Occupational Exposure of Hairdressers to Airborne Hazardous Chemicals: A Scoping Review - Kezic, Sanja; Nunez, Roberto; Babic, Zeljka; Hallmann, Sarah; Havmose, Martin S.; Johansen, Jeanne D.; John, Swen M.; Macan, Marija; Symanzik, Cara; Uter, Wolfgang; Weinert, Patricia; Turk, Rajka; et al. (International Journal of Environmental Research and Public Health, 2022)
Introduction: Exposure to hazardous chemicals released during hairdressing activities from hair care products puts hairdressers at risk of adverse health effects. Safety assessments of hair products are mainly focused on consumers, but exposure for professional hairdressers might be substantially higher. Objective: To identify and assess available research data on inhalation exposures of professional hairdressers. Methods: A systematic search of studies between 1 January 2000 and 30 April 2021 was performed in Medline, Embase, Web of Science and in Cochrane registry, toxicological dossiers of the Scientific Committee on Consumer Safety (SCCS) of the European Commission as well as the German MAK Commission. Studies reporting quantitative data on airborne concentrations of chemicals in the hairdresser's workplace were considered. The outcome was an airborne concentration of chemicals in the working environment, which was compared, when possible, with current occupational exposure limits (OEL) or guidance levels. Results: In total, 23 studies performed in 14 countries were included. The average number of hairdressing salons per study was 22 (range 1-62). Chemicals most frequently measured were formaldehyde (n = 8), ammonia (n = 5), total volatile organic compounds (TVOC) (n = 5), and toluene (n = 4). More than fifty other chemicals were measured in one to three studies, including various aromatic and aliphatic organic solvents, hydrogen peroxide, persulfate, and particulate matter. Most studies reported environmental air concentrations, while personal exposure was measured only in seven studies. The measured air concentrations of formaldehyde, ammonia, and TVOC exceeded OEL or guidance values in some studies. There was large variability in measuring conditions and reported air concentrations differed strongly within and between studies. Conclusion: Hairdressers are exposed to a wide spectrum of hazardous chemicals, often simultaneously. Airborne concentrations of pollutants depend on salon characteristics such as ventilation and the number of customers but also on used products that are often country- or client-specific. For exposure to formaldehyde, ammonia, and TVOC exceeding OELs or guidance values for indoor air was observed. Therefore, occupational exposure should be taken into account by safety regulations for hair care products.
CRIS-Team WoS Importer:2022-04-22
Keywords: airborne exposure; indoor exposure; health effects; inhalation; hairdressers; hair salons